Foundations and applications of group psychotherapy : a sphere of influence - Ettin, Mark F. (Boston : Allyn and Bacon, 1992)
Presents a combination of theories, clinical vignettes, and literary devices to address a broad audience of practitioners, students, trainers, and managers who must understand and work within collective settings.
Includes bibliographical references and index.
Keywords: Group psychotherapy -- History; Small groups; Group Processes; Psychotherapy, Group